PENGARUH FREKUENSI PULSE PENGELASAN GTAW PADA ALUMINIUM ALLOY 6061 - Ari Wibowo; Nugroho Pratomo Aryanto; Cahyo Budi Nugroho; Muhammad Ismail (Politeknik Negeri Batam, 2019)
This paper describes the effect of pulse frequency on the properties of microhardness, porosity and macrostructure in GTAW welding. This study used alluminum 6061 as a base metal and without filler metal. Pulse frequency is varied from 0 Hz to 10 Hz. The macrostructure results showed the maximum penetration depth occured at pulse frequency 6 Hz, while the maximum penetration width occured when did not pulse frequency. Micro hardness testing showed that the maximum hardness occured at pulse frequency 6 Hz while the lowest hardness occured at pulse frequency 10 Hz. AA 6061 welding without metal filler produced porosity which can have an impact on the hardness of the weld metal.